Study of intrauterine growth from birthweight at Maharaj Nakhon Chiang Mai Hospital - Tongsong T. (2014)
Intrauterine growth curve and normogram for newborns at Maharaj Nakhon Chiang Mai Hospital are constructed. Birthweight at various gestational weeks of deliveries were determined within 24 hrs after birth. All 1,311 Thai pregnant women selected, fitted the criteria of inclusion deliveries at Maharaj Nakhon Chiang Mai Hospital from May 1983 to April 1991 (8 yrs). Their gestational age distribution was between 28 wks to 42 wks. Clinical status at birth was satisfactory. There were no obstetric or medical complications during pregnancy. Mean birthweight and standard deviation of newborns for each gestational age at delivery were calculated and presented in tabular and graphic form. Mean birthweight for 40 wks of gestation was 3.144 +/- 382 g. In addition, normogram of 10th, 50th, 90th percentile ranks of birthweight for each gestational age was constructed. These values may be useful as baseline data of intrauterine growth curve to evaluate fetal growth in our population.